Laparoscopic vs Robotic Complete Mesocolic Excision (CME) and Central Vascular Ligation (CVL) in Colonic Carcinomas: A Retrospectively Collected Prospective Study - Charan, Kunda Hrudaya; Mittal, Vinamara; Kochupapy, Rajesh Thengungal; Rajat, Yadav (Journal of Coloproctology, 2025)
Complete Mesocolic Excision (CME) with Central Vascular Ligation (CVL) has emerged as an advanced oncological technique for colon cancer surgery. The adoption of minimally invasive approaches—laparoscopic and robotic—has further refined these procedures. However, comparative data on their clinical efficacy remains limited.A total of 41 patients underwent CME + CVL, with 30 undergoing laparoscopic surgery and 11 receiving robotic-assisted procedures. Key variables assessed included operative time, lymph node yield, postoperative complications, hospital stay, and survival outcomes.The mean patient age was 70.76 years. Malignant neoplasms of the ascending and transverse colon were the most common diagnoses. While both surgical approaches demonstrated comparable oncological outcomes, robotic surgery was associated with faster recovery and reduced postoperative pain, albeit at a higher cost and longer operative time. The survival rate was 93.1%, with a mortality rate of 6.9%. Common postoperative complications included ileus, pneumonia, and anastomotic leaks.Both laparoscopic and robotic CME + CVL are effective for colon cancer treatment. Laparoscopic surgery remains cost-effective and widely accessible, while robotic surgery provides enhanced precision and recovery benefits in select cases. Future research should focus on cost-effectiveness and long-term oncological outcomes.
Keywords: colorectal cancer; complete mesocolic excision (CME); central vascular ligation (CVL); robotic surgery; oncological outcomes